The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1007/s11920-000-0044-0
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives on schizotypal personality disorder

Abstract: Schizotypal personality disorder is the prototype of the schizophrenia-related personality disorders and has been demonstrated to have phenomenologic, biologic, treatment, and outcome characteristics similar to those of schizophrenic patients. These studies suggest that patients with schizotypal personality disorder, like schizophrenic patients, show cognitive impairment, but the impairment is more focal and involves primarily working memory, verbal learning, and sustained attention rather than generalized int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…The pattern of disrupted cingulum FA in the present study is complex but generally consistent with prior work in schizophrenia. Our finding of reduced FA in posterior cingulum (BA31 and BA23) is consistent with schizophrenia work showing similar reductions 4, 8, 11 and posterior cingulum is implicated in visuo-spatial function, memory function and self-referential processing which are areas where SPD individuals evidence deficiencies 65 . The finding of increased FA in anterior cingulum (BA25) is supported by work showing increased FA in left subgenual anterior cingulum white matter (and some other regions) in individuals at high genetic risk for schizophrenia 64 .…”
Section: Discussionsupporting
confidence: 91%
“…The pattern of disrupted cingulum FA in the present study is complex but generally consistent with prior work in schizophrenia. Our finding of reduced FA in posterior cingulum (BA31 and BA23) is consistent with schizophrenia work showing similar reductions 4, 8, 11 and posterior cingulum is implicated in visuo-spatial function, memory function and self-referential processing which are areas where SPD individuals evidence deficiencies 65 . The finding of increased FA in anterior cingulum (BA25) is supported by work showing increased FA in left subgenual anterior cingulum white matter (and some other regions) in individuals at high genetic risk for schizophrenia 64 .…”
Section: Discussionsupporting
confidence: 91%
“…For example, a number of studies (cf. Kline & Cooper, 1986;O'Reilly et al, 2001;Eysenck and Furnham, 1993;Gianotti et al, 2001;Merten and Fischer, 1999;Poreh et al, 1993) reported a positive relationship between creativity and schizotypy, which is associated with dopamine-related genes (Ettinger et al, 2006) and overactivity of subcortical dopaminergic systems (Kirrane and Siever, 2000). Furthermore, dopamine antagonists, generally used as antipsychotics, suppress creativity (Flaherty, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…While both SPD and BPD patients exhibit symptoms that have been linked to temporal and frontal lobe abnormalities, these symptoms differ phenomenologically from one another. Specifically, emotion dysregulation and impulsivity are hallmark features of BPD (Skodol et al, 2002), while blunted affect and executive dysfunction are frequently associated with SPD (Kirrane and Siever, 2000). In this sense, abnormal volume in prefrontal and temporal regions may underlie affect-related symptoms in BPD (Soloff et al, 2008); in SPD, abnormal frontal and temporal lobe volume may be associated with cognitive and/or executive functioning deficits (McCloskey et al, 2005).…”
Section: Introductionmentioning
confidence: 99%